Nanocarrier mediated delivery of insecticides into tarsi enhances stink bug mortality - Sharma, Sandeep; Perring, Thomas M.; Jeon, Su-Ji; Huang, Huazhang; Xu, Wen; Islamovic, Emir; Sharma, Bhaskar; Giraldo, Ysabel Milton; Giraldo, Juan Pablo (Nature communications, 2024)
Current delivery practices for insecticide active ingredients are inefficient with only a fraction reaching their intended target. Herein, we developed carbon dot based nanocarriers with molecular baskets (γ-cyclodextrin) that enhance the delivery of active ingredients into insects (southern green stink bugs, Nezara viridula L.) via their tarsal pores. Nezara viridula feeds on leguminous plants worldwide and is a primary pest of soybeans. After two days of exposure, most of the nanocarriers and their active ingredient cargo (>85%) remained on the soybean leaf surface, rendering them available to the insects. The nanocarriers enter stink bugs through their tarsi, enhancing the delivery of a fluorescent chemical cargo by 2.6 times. The insecticide active ingredient nanoformulation (10 ppm) was 25% more effective in controlling the stink bugs than the active ingredient alone. Styletectomy experiments indicated that the improved active ingredient efficacy was due to the nanoformulation entering through the insect tarsal pores, consistent with fluorescent chemical cargo assays. This new nanopesticide approach offers efficient active ingredient delivery and improved integrated pest management for a more sustainable agriculture. Current insecticide delivery practices are inefficient, with only a fraction reaching the intended target. This study developed carbon dot nanocarriers with molecular baskets to enhance the delivery of insecticides through stink bug tarsal pores, significantly increasing insecticide efficacy.